The effect of match congestion on hip adductor squeeze strength in youth rink hockey players - Quintana-Cepedal, M.; de la Calle, O.; Crespo, I.; Medina-Sánchez, M.; del Valle, M.; Olmedillas, H. (Apunts Sports Medicine, 2024)
Introduction Groin injuries are common among rink hockey players. Monitoring the main risk factors can reduce the likelihood of suffering such injury. The objective of this study was to evaluate the effect of a competitive congestion period on the squeeze strength of the hip adductor muscles in a group of adolescent rink hockey players, and whether the strength reduction exceeded the injury risk threshold (>15%) for sustaining a groin injury.